Aksesibilitas Lahan Parkir dan Lift bagi Individu Difabel pada Pusat Perbelanjaan di Kota Surakarta - Wardany, Ossy Firstanti; Anindyajati, Yasi R; Mujahid, Fauzi Nahwah; Himawanto, Dwi Aries (Indonesian Journal of Disability Studies, 2017)
The purpose of this study was to evaluate the availability and accessibility level of parking facility and lift for difable in Surakarta, especially in the shopping centre. The objects of this study was five shopping centres in Surakarta. The research method that used is evaluation approaches, that assess the extent of an object has been achieved in accordance with the standards of Regulation of the Minister of Public Works of the Republic of Indonesia Number 30 Year 2006 on Technical Guidelines amenities and accessibility In the Building and Environment. Data were analyzed using statistical descriptions by comparing field data with the standard provisions. The results showed that there is no accessible parking lot for difable and on average, as many as 54, 2% lift is accessible and one shopping centre has reached the 73% accesibility lever for the lift. The shopping centre is the right to acquire accessibility in public spaces for difable, it needs to be upgraded and the addition other facilities.